Analema de Vitruvius: dos relógios solares até o relógio de sol plano horizontal - Calil, Marcos Rogério (2008)
Vitruvius, who was born near Rome around the first century BC, introduces in his work Ten Books on Architecture several teachings on Roman architecture, concepts regarding war machines, and also information about the science of his time. His name, place of birth, the dates of his birth and death, and the exact year when the work was written are still open issues, stimulating controversies among specialists who seek to understand the thoughts of the Roman architects who lived in that period. Besides that, several words used within the Ten Books on Architecture are left without translation, because their contextual meaning cannot be understood. The work Ten Books on Architecture, allegedly written by Vitruvius, not only provides the reader with architectural concepts of the first century BC, but also allows a glimpse of the Roman view of the Universe at that time. The aim of the ninth book is explaining Astronomy and the mechanism of the sky for the construction of sundials, and presents the analemma. Vitruvius analemma is a basic geometric analysis preceding the construction of all sundials at that time. However, Vitruvius only describes the construction of the geometric diagram, and not its use and application, a task that is left to mathematicians. He does mention the names of several inventors and their respective sundials, but he does not offer any further details. This work presents, in chapter I, a philological analysis of Vitruvius. Chapter II offers a detailed analysis of Vitruvius book IX, chapter VIII, verse I, where the author refers to many types of sundials and their inventors. After a thorough examination of those sundials, in chapter III the readers will be able to check each stage of the construction of the analemma, commented with the use of translations into Latin, French, Italian, English, Spanish and Portuguese, together with the opinions of commentators. Finally, chapter IV shows an example of how Vitruvius analemma can be applied for the construction of a plane horizontal sundial, following the analysis of Gustav Bilfinger